Evolution of Self-reported Neuropsychiatric Symptoms After Switching from Dolutegravir/Abacavir/Lamivudine to Bictegravir/Emtricitabine/Tenofovir Alafenamide: Results from the Randomized DOBINeuro Trial - Barbara Rossetti; Micol Ferrara; Lucia Taramasso; Francesca Bai; Francesca Lombardi; Nicoletta Ciccarelli; Miriam Durante; Francesca Alladio; Federica Bonazza; Ilaria Rancan; Francesca Montagnani; Antonio Di Biagio; et al. (Infectious Diseases and Therapy)
Abstract Introduction Central nervous system adverse events (AE) have been a cause of discontinuation of dolutegravir-containing therapy, especially in combination with abacavir. The main aim of the study was to evaluate whether the switch to bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) was associated with a reduction in severity and incidence of neuropsychiatric symptoms compared to continued dolutegravir/abacavir/lamivudine (DTG/ABC/3TC). Methods DOBINeuro is a randomized trial enrolling people living with HIV (PLWH) treated with DTG/ABC/3TC for > 6 months and with HIV-RNA < 50 cps/ml for > 12 months. At baseline, PLWH are randomized to continue DTG/ABC/3TC or switch to BIC/FTC/TAF. The original sample size was 50 PLWH per arm, but the enrollment was prematurely stopped due to a delayed recruitment process. Neuropsychiatric symptoms were evaluated by the self-report Symptom Checklist (SCL)-90-R and the Mini-International Neuropsychiatric Interview Plus. Results A total of 41 PLWH were enrolled and underwent randomization: 20 were randomized to continue DTG/ABC/3TC and 21 to switch to BIC/FTC/TAF. At baseline, clinical and laboratory characteristics were homogeneous in the two arms. Switching from DTG/ABC/3TC to BIC/FTC/TAF in virologically suppressed PLWH was associated with an improvement in sleep disorders but not in any other neuropsychiatric symptom. Conclusions Although limited by a low sample size, this study suggests neuropsychiatric tolerability may improve when switching virologically suppressed PLWH from DTG to BIC-based strategies.